The Effect of Motivation and Compensation on Teacher Performance Through Self-Efficacy: Case Study at SMKN 1 Sukabumi City - Supriatno, Empri; H. Suwiryo, Darmo; Hikmat, Asep; Saleh, Munandi (International Journal of Economics, Management and Accounting (IJEMA), 2024)
This study aims to analyze the influence of motivation and compensation on teacher performance through self-efficacy at SMKN 1 Sukabumi City. This research method is quantitative with the type of explanatory research and causal research, and as many as 107 teachers at SMKN 1 Sukabumi City were used as research samples. The data was collected through Google Forms and analyzed using smartPLS version 4.1.0.0 with Outer Model, Inner Model, and Bootstrapping techniques. The results of this study show that: (1) Motivation has a significant negative effect on teacher performance (coefficient -0.217, t-statistic 2.090, p-value 0.037). This means that increasing motivation decreases teacher performance. (2) Compensation had a significant positive effect on teacher performance (coefficient 0.207, t-statistic 2.199, p-value 0.028). Increased compensation improves teacher performance. (3) Motivation had a significant positive effect on self-efficacy (coefficient 0.266, t-statistic 2.940, p-value 0.003). The higher the motivation, the higher the teacher's self-efficacy. (4) Compensation had a significant positive effect on self-efficacy (coefficient 0.314, t-statistic 3.861, p-value 0.000). The higher the compensation, the higher the teacher's self-efficacy. (5) Self-efficacy has a significant positive effect on teacher performance (coefficient 0.511, t-statistic 5.849, p-value 0.000). The higher the self-efficacy, the better the teacher's performance. (6) Motivation influences teacher performance through self-efficacy (coefficient 0.136, t-statistic 2.877, p-value 0.004). Self-efficacy is an important mediator with a contribution of 13.6%. (7) Compensation affects teacher performance through self-efficacy (coefficient 0.160, t-statistic 3.081, p-value 0.002). Self-efficacy is an important mediator with a contribution of 16%.